THE EFFECT OF SOLVENCY, FIRM SIZE, OPERATING CASH FLOW, MANAGERIAL OWNERSHIP ON STOCK RETURN: Pada Perusahaan Sektor Infrastruktur Yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022 - Roffai, Muhammad; Indrati, Menik (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The purpose of this study is to analyze Solvency, Firm Size, Operating Cash Flow, Managerial Ownership on Stock Return. There are four independent variables in this study, namely Solvency (DER), Firm Size (Size), Operating Cash Flow (OCF), Managerial Ownership (MO), and the dependent variable is Stock Return (SR). There are 31 companies that meet the criteria from a total of 65 observations with the object of research on infrastructure sector companies listed on the IDX for the 2020-2022 period. The results of this study indicate that the variables Solvency, Firm Size, Operating Cash Flow, Managerial Ownership simultaneously affect Stock Return. Solvency variable has a negative effect on Stock Return. Firm Size variable has no effect on Stock Return. As well as Operating Cash Flow and Managerial Ownership variables have a positive effect on Stock Return. This research can be taken into consideration for companies to develop strategies that can increase stock returns and proactively face the potential risks of company shares in the future so that investors do not need to look at the size of the company and this research can be used as a basis for making investment decisions by analyzing fundamental data that affects stock price fluctuations, so as to project the expected level of stock return with the least risk.